Putative Nitrogen-Fixing Bacteria Associated With the Rhizosphere and Root Endosphere of Wheat Plants Grown in an Andisol From Southern Chile - Rilling, Joaquin I.; Acuña, Jacquelinne J.; Sadowsky, Michael J.; Jorquera, Milko A. (Frontiers in Microbiology, 2018)
Acidic ash derived volcanic soils (Andisols) support 50% of cereal production in Chile. Nitrogen (N) is essential for cereal crops and commonly added as urea with consequent environmental concerns due to leaching. Despite the relevance of N to plant growth, few studies have focused on understanding the application, management and ecological role of N2-fixing bacterial populations as tool for improve the N nutrition of cereal crops in Chile. It is known that N2-fixing bacteria commonly inhabits diverse plant compartments (e.g., rhizosphere and root endosphere) where they can supply N for plant growth. Here, we used culture-independent and dependent approaches to characterize and compare the putative N2-fixing bacteria associated with the rhizosphere and root endosphere of wheat plants grown in an Andisol from southern Chile. Our results showed significantly greater bacterial loads in the rhizosphere than the root endosphere. Quantitative PCR results indicated that the copy number of the 16S rRNA gene ranged from 10^12~10^13 and 10^7~10^8 g-1 sample in rhizosphere and root endosphere, respectively. The nifH gene copy number ranged from 10^5~10^6 and 10^5 g-1 sample in rhizosphere and root endosphere, respectively. The total culturable bacteria number ranged from 10^9~10^10 and 10^7~10^8 CFU g-1 sample in rhizosphere and 10^4~10^5 and 10^4 CFU g-1 sample in root endosphere using LB and NM-1 media, respectively. Indirect counts of putative N2-fixing bacteria were 10^3 and 10^2~10^3 CFU g-1 sample in rhizosphere and root endosphere using NFb medium, respectively. Sequencing of 16S rRNA genes from randomly selected putative N2-fixing bacteria revealed the presence of members of Proteobacteria (Bosea and Roseomonas), Actinobacteria (Georgenia, Mycobacterium, Microbacterium, Leifsonia and Arthrobacter), Bacteroidetes (Chitinophaga) and Firmicutes (Bacillus and Psychrobacillus) taxa. Differences in 16S rRNA and putative nifH-containing bacterial communities between rhizosphere and root endosphere were shown by denaturing gradient gel electrophoresis (DGGE). This study shows a compartmentalization between rhizosphere and root endosphere for both the abundance and diversity of total (16S rRNA) and putative N2-fixing bacterial communities on wheat plants grown in Chilean Andisols. This information can be relevant for the design and application of agronomic strategies to enhance sustainable N-utilization in cereal crops in Chile.